Pityriasis lichenoides et varioliformis acuta in skin of color: new observations by dermoscopy - Balachandra S. Ankad; Savitha L. Beergouder (Mattioli1885, 2017)
Background: Pityriasis lichenoides is an uncommon skin disease that presents in three different forms: pityriasis lichenoides et varioliformis acuta (PLEVA), pityriasis lichenoides chronica (PLC) and febrile ulceronecrotic-Mucha-Habermann disease. These represent a spectrum of a disease. PLEVA presents as skin eruption of multiple, small, red papules that develop into polymorphic lesions with periods of varying remissions, as well as possible sequels of hyper/hypopigmentation and varicella-like scars. Diagnosis of this condition is mainly clinical, and sometimes clinical differentiation from other conditions may be a difficult task that often requires histological analysis. In this study, PLEVA lesions were examined by dermoscopy, and the significance of specific dermoscopic findings was investigated in order to facilitate their differentiation from other inflammatory conditions. Objectives: To evaluate dermoscopic patterns in PLEVA and to correlate these patterns with histopathology. Materials and methods: The study was conducted at S. Nijalingappa Medical College, Bagalkot. It was an observational case series study and patients were selected randomly. Ethical clearance and informed consent were obtained. PLEVA lesions in early and late phases were evaluated. A manual DermLite 3 (3Gen, San Juan Capistrano, CA) dermoscope attached to a Sony (Cyber Shot DSC-W800, Sony Electronics Inc., San Diego, California, USA, digital, 14 mega pixels) camera was employed. Histopathology was done to confirm the diagnosis. Data was collected and analyzed. Results were statistically described in terms of frequencies and types of dermoscopic patterns. Results: There was a total of 14 patients; 8 males and 6 females. Mean age of patients was 19 years. Mean duration of disease was 7 months. Dermoscopy in early-phase lesions revealed amorphous brownish areas around the hair follicles, dotted vessels, and scaling. Dermoscopy in late-phase lesions showed whitish-structureless areas and central white crust within whitish-structureless rim with scale, focal bluish-grayish areas or centrifugal strands irregularly distributed along the periphery and yellow structures. Red dots and hemorrhage were seen at the center and glomerular vessels at the periphery. Conclusion: PLEVA demonstrates specific dermoscopic patterns that correlate well with histologic changes. New dermoscopic findings are described. Thus, dermoscopy is a good diagnostic tool in the clinical diagnosis of PLEVA.